Construção e controle inteligente de um manipulador robótico com dois graus de liberdade - Silva, Jobson Francisco da (2012)
The present work shows the development and construction of a robot manipulator with two rotary joints and two degrees of freedom, driven by three-phase induction motors. The positions of the arm and base are made, for comparison, by a fuzzy controller and a PID controller implemented in LabVIEW® programming environment. The robot manipulator moves in an area equivalent to a quarter of a sphere. Experimental results have shown that the fuzzy controller has superior performance to PID controller when tracking single and multiple step trajectories, for the cases of load and no load